Loss Aversion and Trade Policy - Freund, Caroline; Özden, Çağlar (World Bank, Washington, D.C., 2013)
This paper provides new survey evidence showing that loss aversion and reference dependence are important in shaping people's perception of trade policy. Under the assumption that agents' welfare functions exhibit these behavioral elements, we analyze a model with a welfare-maximizing government and with the lobbying framework of Grossman and Helpman (1994). The policy implications of the augmented models differ in three important ways. One, there is a region of compensating protection, where a decline in the world price leads to an offsetting increase in protection, such that a constant domestic price is maintained. Two, protection following a single negative price shock will be persistent. Three, irrespective of the extent of lobbying, there will be a deviation from free trade that tends to favor loss-making industries. The augmented models are more consistent with the observed structure of protection, and in particular, explain why many trade policy instruments are explicitly designed to maintain prices at a given level.